2011
DOI: 10.1185/03007995.2011.567255
|View full text |Cite
|
Sign up to set email alerts
|

Remission of major depressive disorder without adverse events: a comparison of escitalopram versus serotonin norepinephrine reuptake inhibitors

Abstract: Treatment of adult MDD patients with escitalopram was significantly more likely to result in remission without concurrent AEs compared to treatment with current SNRIs. Study limitations include focus on only the initial 8 weeks of treatment and exclusion of trials for which individual patient data were not obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Consequently, venlafaxine has a higher antidepressant effect than tricyclic antidepressant drugs. Venlafaxine has slightly different adverse effects in comparison to SSRIs; it can cause hypo-and hypertension, insomnia and weight loss and gain [4]. In the psychiatric ward, the physician decided to administer lithium carbonate, a prophylactic drug, which definitely improved depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, venlafaxine has a higher antidepressant effect than tricyclic antidepressant drugs. Venlafaxine has slightly different adverse effects in comparison to SSRIs; it can cause hypo-and hypertension, insomnia and weight loss and gain [4]. In the psychiatric ward, the physician decided to administer lithium carbonate, a prophylactic drug, which definitely improved depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a transient moderate form of major depression was treated by the selective serotonin reuptake inhibitor citalopram [3]. A severe form of major depression was treated by the selective serotonin and noradrenaline reuptake inhibitor venlafaxine and lithium [4,5]. A severe chronic form of major depression was treated by the selective dopamine and noradrenaline reuptake inhibitor bupropion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Escitalopram is the most selective among SSRIs, with proven efficacy in treating major depressive disorder and onset of antidepressant activity evident within 1–2 weeks of treatment initiation (Signorovitch et al . ). It seems that escitalopram is one of the best treatments for depression in terms of efficacy and acceptability, with low rates of discontinuation due to adverse (Bielski et al .…”
Section: Methodsmentioning
confidence: 97%
“…SNRIs, such as venlafaxine, are more effective in the treatment of major depression than SSRIs [11]. In a meta-analysis, it was shown that the adult antidepressant treatment with escitalopram, an SSRI, compared to the treatment with duloxetine, a 5-HT and noradrenaline reuptake inhibitor, was more effective and resulted in fewer adverse effects [12].…”
Section: Noradrenalinementioning
confidence: 99%